Investigation of a two-dimensional model on Cu2+ recovery in bioemectrochemical system. Issue 1 (1st January 2023) - Cai, Wenfang; Wang, Yunhai
Abstract: A novel microbial fuel cell (MFC) was designed to recover Cu 2 + from simulated electroplating wastewater. The BES has two chambers separated by a bipolar membrane and two cathodes. To explore the rate controlling step affecting Cu 2+ deposition rate, spatial mass distribution and its deposition process during Cu 2+ deposition on MFC cathode. A two-dimensional, transient model was built to study the factors that limiting Cu 2 + deposition in MFC. We found that the formation of ion scarcity zone would decrease Cu 2+ deposition rate, which leading to mass transfer limiting Cu 2+ reduction on cathode surface (x=0 m). While near the cathode tip (x=0.02 m), the highest deposition rate and thickness was obtained. Furthermore, diffusion and electro-migration of Cu 2+ were synergistic to improve Cu 2+ reduction efficiency, and electro-migration of Cu 2+ had a great impact on Cu 2+ transferring from electrolyte domain to electrode surface. This research provided a new studying direction for heavy metal wastewater treatment and metal separation and recovery in the electroplating industry to improve metal ions deposition rate.